2017
DOI: 10.1186/s12882-017-0702-7
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2, 3-dioxygenase (IDO) increases during renal fibrogenesis and its inhibition potentiates TGF-β 1-induced epithelial to mesenchymal transition

Abstract: BackgroundIndoleamine 2, 3-dioxygenase (IDO) is an immunomodulatory molecule that has been implicated in several biological processes. Although IDO has been linked with some renal diseases, its role in renal fibrosis is still unclear. Because IDO may be modulated by TGF-β1, a potent fibrogenic molecule, we hypothesized that IDO could be involved in renal fibrosis, especially acting in the TGF-β1-induced tubular epithelial-mesenchymal transition (EMT). We analyzed the IDO expression and activity in a model of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Our results demonstrated that IDO protein expression was markedly increased in UUO mice. This observation is in line with a previous study by Matheus et al, who showed that IDO expression and activity increased in the renal tissue of rats subject to seven days of UUO [11]. Moreover, we and others have reported that IDO activity is elevated in CKD patients, and correlated with disease severity [3,4,[20][21][22][23].…”
Section: Discussionsupporting
confidence: 93%
“…Our results demonstrated that IDO protein expression was markedly increased in UUO mice. This observation is in line with a previous study by Matheus et al, who showed that IDO expression and activity increased in the renal tissue of rats subject to seven days of UUO [11]. Moreover, we and others have reported that IDO activity is elevated in CKD patients, and correlated with disease severity [3,4,[20][21][22][23].…”
Section: Discussionsupporting
confidence: 93%
“…It could be useful to study the levels of IDO in these two stages which could be better for assessing kidney function. Secondly, the sample size in our study was still not large enough although bigger than a previous study [ 9 , 16 ]. But the correlation coefficient of eGFR and IDO was pretty high, and the ROC showed that IDO was a promising biomarker for CKD enhancing the negative relationship between IDO and CKD.…”
Section: Discussionmentioning
confidence: 68%
“…Mutations in the cystic fibrosis have been reported to have a defect in IDO expression and resulted in intensified fibrosis [ 6 ]. On the contrary, kidney studies revealed elevated expression of IDO in tubules in the unilateral ureteral obstruction model and transforming growth factor- β stimulated MDCK cells [ 9 ] as well as diabetic nephropathy patients [ 10 ]. Our study also revealed increased activity of IDO in CKD patients, especially in CKD stage 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β2 could induce EMT in HLEcs (26). The signaling pathways that are activated in response to TGF-β2 and lead to EMT have primarily been conducted in vitro using NMuMG, MdcK and HacaT cell lines (27)(28)(29)(30). In the present study, EMT in HLEB-3 cells was activated when cells were incubated with TGF-β2, providing new insight for further exploring the potential functional relationship between SNAI1 and HdAc1 in the pathogenesis of PcO and its underlying mechanisms.…”
Section: Discussionmentioning
confidence: 66%